Design and development of Ca-Mg-Fe-Ti-oxides based perovskite for high sensitive humidity sensors and wound healing applications / Ashis Tripathy - Ashis, Tripathy (2017)
Armalcolite, which is a rare ceramic mineral and normally found in the lunar earth, was synthesized by solid-state step-sintering. The in situ phase-changed novel ceramic nanocrystals of Ca-Mg-Fe-Ti based oxides (CMFTO), their chemical reactions, and bonding with polydimethylsiloxane (PDMS) were determined by x-ray diffraction, infrared spectroscopy, and microscopy. Water absorption of all the CMFTO was high. Different types of humidity sensors were developed using three distinct principles. The lower dielectric loss tangent value was obtained for the CMFTO ceramic sintered at 1050 °C (S1050) (0.155 at 1 MHz) and S1050/PDMS nanocomposite (0.002 at 1 MHz) film, which was made by spin coating at 3000 rpm. The excellent flexibility (Young’s modulus≈0.27 MPa and elongation >90%), viscoelastic property (tan = E″/E′: 0.225) and glass transition temperature (Tg: -58.5 °C) were obtained for S1050/PDMS film. Humidity dependent capacitive, resistive, and dielectric response of S1050 electroceramic was studied successfully. The S1050 electroceramic based capacitive sensor showed excellent sensitivity of 3000% as well as fast response (14.5 s) and recovery (34.27 s) times, which are extremely lower than those of the other conventional capacitive humidity sensors. The impedance and dielectric sensors showed improved sensitivity of 0.23 MΩ/Δ%RH and ~2310%, respectively. The response and recovery times were 20 and 40 s, respectively for resistive sensor and for dielectric sensor, they were 18 and 35 s, respectively. All the three capacitive, resistive and dielectric humidity sensors showed extreamly low hysteresis and high stability. Therefore, best sensing performance of the flexible S1050/PDMS composite film (306%) based humidity sensor was found at 100 Hz, better than conventional materials. In order to evaluate the biocompability of the S1050 and S1050/PDMS composite film based sensors with the direct contact to dermal surface, an in vitro study was employed using human dermis fibroblast cells. It showed that both the materials have good biocompatibility and can thus be suitable for measuing the humidity at the skin and inner prosthetic surfaces. To evaluate the drug carrying capacity of the present nanomaterials with the direct contact to dermal surface for wound healing applications, an in vivo assay was performed by aplying some hydrogels on rat’s dorsal wounds. To investigate the histological and immunohistochemical effects of the curcumin drug loaded S1050 nanocomposite hydrogels disperred in poly(vinyl alcohol) solution, an in vivo cutaneous full-thickness excisional wound rat model was adopted using adult male sprague dawley (SD) rats. The normal and diabetic (created by injection of Streptozotocin (dosage: 55mg/kg)) rats were wounded of size 2 cm diameter at the posterior neck area. The rats were topically applied with 0.2 ml gels of curcumin, S1050, and curcumin loaded S1050 hydrogel separately for 14 days. Many interesting improved results were found for diabetic subjects using present hydrogels. Briefly, the in vivo results revealed improved wound contraction and tissue regeneration in diabetic rats applied with curcumin, S1050, and curcumin loaded S1050 hydrogels as compared with diabetic rats using normal hydrogel. Moreover, beside sensors, the novel S1050 (i.e. armalcolite based nanocomposites) would be potential drug carrier for wound healing applications since their hydrogels showed as biocompatible, nontoxic, nonimmunogenic, and efficient drug carriers.